Cell proliferation in kidney carcinoma is inhibited by lncRNA GASL1. (June 2019) - Dong, Jianping; Zheng, Shiping; Yang, Xiaoyan; Song, Xiuyan
Long noncoding RNA (lncRNA) GASL1 was identified as a novel lncRNA, which plays an important role in the proliferation and apoptosis of cells. This study aimed to compare the expression of GASL1 mRNA in kidney cancer cells and normal cells and detect the biological role of GASL1 in kidney cancer cell line A498. Polymerase chain reaction (PCR) was performed to examine the expression of GASL1 mRNA in kidney cancer tissues, normal tissues, and the cell lines. GASL1 overexpression was achieved in kidney cancer cell lines A498 through transfection. MTT was used to detect the effects of GASL1 overexpression in A498 cells. GASL1 mRNA was significantly overexpressed in adjacent normal tissues compared with renal cell carcinoma. The expression of GASL1 is lower in kidney cancer cell lines than in normal kidney epithelium cell line HREpiC. Overexpression of GASL1 inhibits the proliferation of renal carcinoma cell lines. GASL1 mRNA was down-regulated in kidney cancer tissues and may play a role in kidney cancer cell proliferation.